2011
DOI: 10.3141/2231-11
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Value of Travel Time Savings by Using Large-Scale Household Survey Data from Japan

Abstract: Expressways provide road users with reduced travel time and safer driving conditions for a toll. The toll charge has been one of the most important issues in expressway planning. The user's willingness to pay for saving travel time by using an expressway service is one of the most important factors in examining toll charges for expressways. A large Japanese database was used to empirically estimate road users' value of travel time savings (VTTS). The results showed that the estimated VTTS of business travel wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The values of estimated in-vehicle travel time and connection time are 115.4 and 120.6 JPY/min, respectively. Past empirical studies also showed a similar value for travel time, for example, Kato et al (19) showed that the value of travel time for business travelers was 125 JPY/ min, which is estimated from the Interregional Travel Survey 2005; Kato and Onoda (20) showed that the value of travel time was 165.9 JPY/min, which is estimated from the Interregional Travel Survey 2000. This reveals that most of the O-D pairs have longer travel times for rail +bus than for other travel modes, while many O-D pairs have cheaper travel costs for rail-+bus than for other travel modes.…”
Section: Estimation Resultsmentioning
confidence: 71%
“…The values of estimated in-vehicle travel time and connection time are 115.4 and 120.6 JPY/min, respectively. Past empirical studies also showed a similar value for travel time, for example, Kato et al (19) showed that the value of travel time for business travelers was 125 JPY/ min, which is estimated from the Interregional Travel Survey 2005; Kato and Onoda (20) showed that the value of travel time was 165.9 JPY/min, which is estimated from the Interregional Travel Survey 2000. This reveals that most of the O-D pairs have longer travel times for rail +bus than for other travel modes, while many O-D pairs have cheaper travel costs for rail-+bus than for other travel modes.…”
Section: Estimation Resultsmentioning
confidence: 71%
“…Access and egress time. It is commonly found that access and egress times by walking are weighed more negatively than IVT in the main stage of a trip (Kato et al, 2011;Arentze and Molin, 2013;Wardman et al, 2016). As seen in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…VOT for IVT of car is the most studied aspect in travel behavior research. The average VOT across trip purposes in Japan (Kato et al, 2011(Kato et al, ) (data of 2005, the Netherland (Arentze and Molin, 2013) (data of 2012), UK (Department for Transport of UK, 2014) (data of 2010 to 2012), and USA (USDOT, 2015) (data of 2015) are roughly 0.22, 0.19, 0.37, and 0.26 in USD/minute, respectively. In China, the number of studies reporting VOT of car travel is still limited but increasing.…”
Section: Resultsmentioning
confidence: 99%
“…A variável de análise (variável dependente), em geral, é representada pelos padrões de atividades/viagens definidos através de um processo individual de escolha. (ANTONIOU et al, 2007;GOSSEN, 2004;FORINASH;KOPPELMAN, 1993;KATO et al, 2011;MCCAFFERTY;HALL, 1982;MISHRA et al, 2013;PAULSSEN et al, 2014;TIMMERMANS et al, 2002;WANG et al, 2017;YE X et al, 2017) e mais especificamente no estudo de viagens encadeadas (LEE et al, 2017;RUAN et al, 2012;BUEHLER e HAMRE, 2015;LEE et al, 2007) Conforme descrito anteriormente, os modelos Logit são os mais comumente usados para modelar escolhas discretas de viagens baseadas em atividades. Com relação ao modelo Logit Multinomial, há importantes premissas que o caracterizam, como a independência dos termos aleatórios das utilidades, a homogeneidade de resposta entre indivíduos e a homogeneidade da variância dos erros (BHAT; KOPPELMAN, 1999).…”
Section: Objetivos Específicosunclassified